Study on Efficiency of LoRa Node for Long-Distance Communication in the Micro-Hydropower Plant Control System - vilachit, souvanhny (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The monitoring and controlling process in electricity production of hydro-power plants, relating to water management, generated electric and system maintenance are essential. It affects electricity production efficiency and safety. As real-world condition, the monitoring station and supervisory control center are quite far from each other with hard-to-reach environment surrounded by bush and trees, a wireless communication system is highly required. This research aims to design a wireless communication network utilizing LoRa technology for the purpose of monitoring water levels in a hydropower plant. The study was conducted by establishing a water level monitoring station and a wireless communication station at the Nam Mang 3 Hydropower plant, situated in Phu Khao Khuai National Park, Thoulakhom District, Vientiane Province. In the communication experiment, the LoRa module operated at a frequency of 433 MHz over a distance of 3,632 meters, with a microcontroller serving as the processor to interface with the central control system and various measurement devices. Data on water levels, signal strength, and communication speed were recorded for performance analysis. The findings indicate that LoRa technology effectively communicates and monitors water level data within a challenging forest environment characterized by high mountain barriers, achieving an average signal strength of -108.08 dBm. This suggests that LoRa is suitable for long-range communication in dam environments, though the communication capability may vary depending on the specific types of LoRa modules used.